Chance, luck and a fortunate finding: a new species of watersnake of the genus Helicops Wagler, 1828 (Serpentes: Xenodontinae), from the Brazilian Pantanal wetlands - Moraes-Da-Silva, Antonio; Amaro, Renata Cecília; Nunes, Pedro M. Sales; Strüssmann, Christine; Teixeira, Mauro Junior; Andrade, Albedi Jr.; Sudré, Vinícius; Recoder, Renato; Rodrigues, Miguel Trefaut; Curcio, Felipe Franco (Zootaxa, 2019)
We describe a new watersnake of the genus Helicops based on a single specimen found in the northern limit of the Brazilian Pantanal. Immediately after collection, the unique features of color pattern and head proportions prevented us to attribute this specimen to any other congener. Further comparisons revealed that the combination of entire nasal scales, a distinctively acuminate snout, high dorsal and supralabial counts, as well as a dorsal pattern with chain-like spot rows and a venter with vivid and peculiar orange markings confirmed that the specimen represented a new species. Molecular data supported our morphological conclusion recovering the new species deeply nested within Helicops terminals, sister to a clade composed by H. carinicaudus and H. nentur. Our discovery represents a rare instance of a snake species restricted to the Brazilian Pantanal, but we refrain from considering it a Pantanal endemic until further records allow more considerations on distributional patterns.